Synthesis of Metabolic Amino acid Precursors: Tools for Selective Isotope Labeling in Cell-Based Protein Overexpression - Lichtenecker, Roman J.; Schörghuber, Julia; Bisaccia, Marilena (Synlett, 2015)
The rapid development of biomolecular NMR spectroscopy in the last decade(s) has paved the way for novel insights into the structure, dynamic properties, as well as the interaction of proteins. However, NMR data interpretation of large protein complexes is only feasible if the corresponding sample is selectively enriched in NMR active nuclei (13C and 15N) and/or 1H-depleted by 2H incorporation. One important strategy for selective protein isotope labeling is given by the addition of metabolic amino acid precursor compounds to the growth medium of a protein-overexpressing microorganism. Herein, we highlight the synthetic concepts to access these precursors from commercially available isotope sources.1 Introduction2 Aliphatic Residue Precursors3 Aromatic Residue Precursors4 Precursors of Other Labeled Residues5 Conclusions
Keywords: isotope labeling; protein NMR; α-keto acids; protein overexpression; amino acid precursors